New Unnatural Gallotannins: A Way toward Green Antioxidants, Antimicrobials and Antibiofilm Agents - Zuzana Hricovíniová; Šárka Mascaretti; Jana Hricovíniová; Alois Čížek; Josef Jampílek (MDPI AG, 2021)
Nature has been a source of inspiration for the development of new pharmaceutically active agents. A series of new unnatural gallotannins (GTs), derived from d-lyxose, d-ribose, l-rhamnose, d-mannose, and d-fructose have been designed and synthesized in order to study the protective and antimicrobial effects of synthetic polyphenols that are structurally related to plant-derived products. The structures of the new compounds were confirmed by various spectroscopic methods. Apart from spectral analysis, the antioxidant activity was evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging and iron reducing power (FRAP) assays. Antibacterial activity of compounds was tested in vitro against Staphylococcus aureus ATCC 29213, Enterococcus faecalis ATCC 29212 (reference and control strains), three methicillin-resistant isolates of S. aureus, and three isolates of vancomycin-resistant E. faecalis. For screening of antimycobacterial effect, a virulent isolate of Mycobacterium tuberculosis and two non-tuberculous mycobacteria were used. Furthermore, antibiofilm activity of structurally different GTs against S. aureus, and their ability to inhibit sortase A, were inspected. Experimental data revealed that the studied GTs are excellent antioxidants and radical-scavenging agents. The compounds exhibited only a moderate antibacterial effect against Gram-positive pathogens S. aureus and E. faecalis and were practically inactive against mycobacteria. However, they were efficient inhibitors and disruptors of S. aureus biofilms in sub-MIC concentrations, and interacted with the quorum-sensing system in Chromobacteriumviolaceum. Overall, these findings suggest that synthetic GTs could be considered as promising candidates for pharmacological, biomedical, consumer products, and for food industry applications.